Efektivitas Pengawasan Dinas Tenaga Kerja Dan Transmigrasi Wilayah Serang 1 Dalam Penerapan Keselamatan Dan Kesehatan Kerja Studi Di PT. Krakatau Baja Kontruksi Cilegon - Annisa Nur Jarnita; Hasuri Waseh; Rahmawati (CV. Multi Kreasi Media, 2025)
This research aims to determine the effectiveness of the supervision conducted by the Manpower and Transmigration Office of Serang Region I in addressing Occupational Safety and Health (OSH) issues at PT. Krakatau Baja Kontruksi, Cilegon City. The study applies the organizational effectiveness theory of Gibson, Ivancevich, and Donnelly using the goal achievement approach and the systems approach consisting of input, process, output, and environment dimensions. The method used is descriptive qualitative with exploratory approach and data collection techniques through interviews, observation, and documentation. The results show that OSH supervision has been carried out but is not yet optimal due to several shortcomings, such as uneven distribution of training, delays in following up violations, limited budget, and lack of firm sanctions from the Manpower and Transmigration Office of Serang Region I. Nevertheless, the company has made internal improvements, such as reporting violations through P2K3 and gradually implementing training programs. This research recommends enhancing OSH socialization, increasing the number of inspectors, and strengthening the reporting and evaluation system to support zero accident efforts in the workplace.